Prototype of Monitoring and Controlling Rice Field Irrigation Based on Internet of Things - Heri Sudibyo; Asril; Andrey Eka Rahman Sidiq (Komunitas Dosen Indonesia, 2025)
The advancement of Internet of Things (IoT) technology has significantly impacted various sectors, including agriculture, by enabling automation and real-time monitoring. In rice farming, one persistent challenge is the reliance on manual irrigation, which often results in water waste, increased labor demands, and reduced crop yields due to delayed or inconsistent water management. This research aims to design and implement a prototype IoT-based irrigation system to address these inefficiencies. The proposed system allows farmers to remotely monitor and control water flow using a smartphone via the Telegram messaging application. Telegram is chosen for its ubiquity, cross-platform compatibility, and ease of use, making it accessible to farmers without specialized technical skills. The system uses an ESP32 microcontroller as the core processor, an HC-SR04 ultrasonic sensor to detect water levels, and an SG90 servo motor to automate the sluice gate mechanism. A 16x2 LCD is integrated for real-time field display. Telegram enables interactive control through command inputs (e.g., opening and closing gates) and automated notifications, providing continuous status updates. The system operates autonomously based on preset water level thresholds but also supports manual override. Testing results show that the system is responsive and accurate (within ±1 cm), and it significantly reduces the need for frequent field visits. This solution enhances irrigation precision, reduces labor, and contributes to better water resource management. By integrating commonly available digital tools with low-cost hardware, the prototype offers a practical and scalable solution for improving agricultural productivity, especially in remote rural areas.